Minimizing VPD Fluctuations Maintains Higher Stomatal Conductance and Photosynthesis, Resulting in Improvement of Plant Growth in Lettuce - Inoue, Takayasu; Sunaga, Motoo; Ito, Mutsuhiro; Yuchen, Qu; Matsushima, Yoriko; Sakoda, Kazuma; Yamori, Wataru (Frontiers in Plant Science, 2021)
Vapor pressure deficit (VPD) is considered to be one of the major environmental factors influencing stomatal functions and photosynthesis, as well as plant growth in crop and horticultural plants. In the greenhouse cultivation, air temperature and relative air humidity are regulated by switching on/off the evaporative systems and opening/closing the roof windows, which causes VPD fluctuation. However, it remains unclear how VPD fluctuation affects photosynthetic and growth performance in plants. Here, we examined the effects of the VPD fluctuation on the photosynthetic and growth characteristics in lettuce (Lactuca sativa L.). The parameters for gas exchange and chlorophyll fluorescence and biomass production were evaluated under the conditions of drastic (1.63 kPa for 6 min and 0.63 for 3 min) or moderate (1.32 kPa for 7 min and 0.86 kPa for 3 min) VPD fluctuation. The drastic VPD fluctuation induced gradual decrease in stomatal conductance and thus CO2 assimilation rate during the measurements, while moderate VPD fluctuation caused no reduction of these parameters. Furthermore, data showed moderate VPD fluctuation maintained leaf expansion and the efficiency of CO2 diffusion across leaf surface, resulting in enhanced plant growth compared with drastic VPD fluctuation. Taken together, fine regulation of VPD can be crucial for better plant growth by maintaining the photosynthetic performance in lettuce. The present work demonstrates the importance of VPD control during plant cultivation in plant factories and greenhouses.